THU0029 Ctla-4-ig treatment induces modulation of b-cell function and differentiation. (12th June 2018) - Thiel, J.; Lorenzetti, R.; Janovska, I.; Smulski, C.R.; Walter, L.; Staniek, J.; Schleyer, T.; Voll, R.E.; Venhoff, N.; Rizzi, M.
Abstract : Background: CTLA-4 modulates T-cell activation by inducing inhibitory signalling in T-cells. To date the direct effect of CTLA-4-Ig (abatacept) on B-cells has not been studied in detail. We hypothesise that CTLA-4 modulates B-cell function, B-cell homeostasis and B-cell receptor signalling in a T-cell-dependent and T-cell-independent manner. Objectives: To assess the impact of abatacept on 1. B-cell activation and function in vitro ; 2. B-cell signalling in vitro; 3 maintenance and specificity of memory B-cells specific for citrullinated protein antigens in vivo. Methods: The time kinetic of CD80 and CD86 expression was measured by flow cytometry on isolated B-cells after stimulation via CD40, IL-21R, TLR9, and BCR in presence and absence of CTLA-4-Ig. Human B-cells lines (BJAB) deficient either for CD80 or CD86 were created using the CRISPR Cas9 technology and the effect of abatacept on CD80 respectively CD86 expression was assessed in these K.O. cell lines. CD80 and CD86 internalisation upon abatacept binding was studied by fluorescence microscopy. The effect of abatacept on PI3K-, NF-kB, PLCy-signalling and Ca-flux in B-cells was assessed. The effect of CTLA-4-Ig in vivo on the pool of memory cells specific for anti-citrullinated protein antigens was studied by limiting dilution assays performed before and during CTLA-4-Ig treatment. Results: The expression of CD80 and CD86 on isolated human B-cells peaked at day 2–3 of culture after stimulation with CD40-L and IL-21. CTLA-4-Ig led to a decrease in CD80 and CD86 expression. These results were confirmed in human B-cell lines deficient either for CD80 or CD86. By fluorescence microscopy we were able to demonstrate, that abatacept treatment of cultured B-cells leads to a reduction in CD80 and CD86 expression mediated by a mechanism that involves internalisation of the receptors and bound CTLA-4-Ig. To test if CTLA-4-Ig binding activates signalling pathways, we stimulated B-cells with CTLA4-Ig or via BCR or CD40. We detected phosphorylation of p65 indicating activation of the canonical NF-kB pathway. The effect of CTLA-Ig in vivo on the pool of memory cells specific for autoantigens (anti-citrullinated protein antigens) was studied by limiting dilution assays in patients with rheumatoid arthritis. This assay is based on polyclonal stimulation of memory B-cells that leads to blast formation and antibody secretion in the supernatant. We performed limiting dilution experiments before and after start of CTLA-4-Ig treatment and observed a significant reduction of the absolute frequency of citrullinated antigen specific memory B-cells in response to treatment. Conclusions: CTLA-4-Ig-treatment leads to a decrease in B-cells' CD80 and CD86 expression, mediated by a mechanism that involves internalisation of the receptors and bound CTLA-4-Ig. CTLA-4-Ig activates the canonical NF-kB pathway in B-cells. In vivo CTLA-4-Ig treatment reduces the frequency of citrullinated antigen specific memory B-cells in patients with rheumatoid arthritis. Disclosure of Interest: J. Thiel Grant/research support from: Research Grant from Bristol Myers Squibb, R. Lorenzetti: None declared, I. Janovska: None declared, C. Smulski: None declared, L. Walter: None declared, J. Staniek: None declared, T. Schleyer: None declared, R. Voll: None declared, N. Venhoff: None declared, M. Rizzi Grant/research support from: Research Grant from Bristol Myers Squibb